Incidence of pelvic inflammatory disease in backache in females - Sachdeva, Parminder Kaur; Dahiya, Ashish; Singh, Ravinder (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2016)
Background: Treatment of low backache has always been a question for the doctors due to its vast differential diagnosis. Pelvic inflammatory disease (PID) is one of the most frequent infections seen in reproductive age women and is associated with major clinical and pelvic health problem. The present study will be undertaken to study the incidence of pelvic inflammatory diseases of backache in females. Methods: A prospective epidemiological study was done on 250 female patients in the department of obstetrics and gynaecology of Medical College, Mullana, Haryana, India during the period from September 2013 to May 2015. In this study, patients were divided into 2 groups as per their complaints. Group 1 included the patients those whose underlying complaint which was backache and had per vaginal discharge (provisionally diagnosed pelvic inflammatory disease) and group 2 included patients who had backache without any known skeletal problem and without per vaginal discharge. Patients were thoroughly interviewed and physically examined in the presence of female attendant to determine the underlying cause of backache. Follow up of the patients was done on 2, 4, 8 weeks. Results: In this study, out of 250 female patients 216 were diagnosed as pelvic inflammatory disease as the under lying pathology along with backache that comprised of 86.4% of the study group. Out of 250 patients, 53.2% were of low socio economic status. Maximum number of patients of backache with discharge per vagina was of age group of 40-50 years which makes them 35.6% of the total patients of backache. Conclusions: From present study, pelvic inflammatory disease is a major risk factor causing the low backache in patients and hampering their day to day activities.